Delayed Diagnosis and Diagnostic Pathway of ALS Patients in Portugal: Where Can We Improve? - Falcão de Campos, Catarina; Gromicho, Marta; Uysal, Hilmi; Grosskreutz, Julian; Kuzma-Kozakiewicz, Magdalena; Oliveira Santos, Miguel; Pinto, Susana; Petri, Susanne; Swash, Michael; de Carvalho, Mamede (Frontiers in Neurology, 2021)
Background: Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease with unsatisfactory treatment options. Best management and recruitment into clinical trials requires early diagnosis. However, diagnosis is often delayed. Analysis of the diagnostic pathway and identification of the causes of diagnostic delay is imperative. Methods: We studied a cohort of 580 ALS patients followed in our ALS clinic in Lisbon. Demographic, disease and sociocultural factors were collected. Time from first symptom onset to diagnosis, the specialist’s assessment and investigations requested were analyzed. Predictors of diagnostic delay were evaluated by multivariate linear regression, adjusting for potential confounders. Results: The median diagnostic delay from first symptom onset was 10 months. Spinal-onset, slower disease progression, cognitive symptoms at onset and lower income were associated with increased diagnostic delay. Most patients were first assessed by General Practitioners. Patients who were first evaluated by a Neurologist were more likely to be correctly diagnosed, decreasing time to diagnosis. Electromyography was decisive in establishing the diagnosis. Conclusions: Late referral from non-Neurologists to a Neurologist is a potentially modifiable factor contributing to significant diagnostic delay. Educational interventions targeted to non-Neurologists physicians, in order to increase awareness of ALS and, consequently promote early referral to a Neurologist at a tertiary center, will be important in reducing diagnostic delay.